2015
DOI: 10.1021/acs.jafc.5b00443
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Absorption, Metabolism, and Excretion of Cocoa Flavanols in Humans

Abstract: Cocoa is rich in a subclass of flavonoids known as flavanols, the cardiovascular health benefits of which have been extensively reported. The appearance of flavanol metabolites in the systemic circulation after flavanol-rich food consumption is likely to mediate the physiological effects on the vascular system, and these levels are influenced by numerous factors, including food matrix, processing, intake, age, gender, or genetic polymorphisms, among others. This review will focus on our current understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 75 publications
1
29
0
Order By: Relevance
“…We demonstrate in this study that cocoa flavonoids, when present together as in the cocoa extract, have a notable anti-inflammatory effect in polarized macrophages, as previously demonstrated for other foods, for example, pomegranate juice [20]. Although the concentration in plasma of cocoa flavonoids and their metabolites is known to be low in humans [46, 47], research based on flavonoid-enriched cocoa-derived products with enhanced bioavailability is ongoing [4850]. In this context, it has been reported that, in healthy subjects, (−) epicatechin reached maximal concentrations of 5.92 ± 0.60  μ mol/l 2 h after the consumption of 0.375 g cocoa/kg body wt.…”
Section: Discussionsupporting
confidence: 57%
“…We demonstrate in this study that cocoa flavonoids, when present together as in the cocoa extract, have a notable anti-inflammatory effect in polarized macrophages, as previously demonstrated for other foods, for example, pomegranate juice [20]. Although the concentration in plasma of cocoa flavonoids and their metabolites is known to be low in humans [46, 47], research based on flavonoid-enriched cocoa-derived products with enhanced bioavailability is ongoing [4850]. In this context, it has been reported that, in healthy subjects, (−) epicatechin reached maximal concentrations of 5.92 ± 0.60  μ mol/l 2 h after the consumption of 0.375 g cocoa/kg body wt.…”
Section: Discussionsupporting
confidence: 57%
“…This strengthens the case for a dose of 100 mg of epicatechin in a cocoa product, rather than 200 mg flavanols (with 46 mg epicatechin) as recently approved by the European Food and Safety Authority (EFSA), to contribute to healthy blood flow (EFSA, ). As the sugar present in chocolate (Njike et al ., ; Grassi et al ., ), and numerous other factors except age (Rodriguez‐Mateos et al ., ) affect the absorption, metabolism and excretion of the flavanols (Cifuentes‐Gomez et al ., ), the generally recommended daily consumption of 200 mg of flavanols (with 46 mg epicatechin) should be revised.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that many factors can interfere with the effect of the bioactive compounds of foods, such as complex food matrix, the chemical form of each substance, the structure and amount of other compounds present in the diet, the rate of gastric emptying and individual metabolism (Cifuentes‐Gomez, Rodriguez‐Mateos, Gonzalez‐Salvador, Alañon, & Spencer, ; Oliveira & Bastos, ). The cocoa drink in which UBF was added showed a higher fiber content, which may have reduced the gastric emptying rate, the slower access of cocoa flavonoids in the intestine and reduced absorption of epicatechin free.…”
Section: Discussionmentioning
confidence: 99%